Labour in northern USSR - Armstrong, Terence (Polar Record, 1967)
One of the biggest problems facing those who seek to exploit the natural riches of the north is the attraction and retention of a labour force. This problem is sometimes more intractable even than those posed more directly by the remoteness of the locality and the harshness of the environment. No easy or simple solution has been found, but it may be of interest to record some of the recent steps taken by the Soviet Government towards its solution.